The Effectiveness of Using the Google Classroom Educational Platform in Teaching Mathematics Curricula from the Teachers' Point of View (Journal Of Educational and Psychological Researches, 2023)
The study aims to find out the effectiveness of using the Google classroom educational platform in teaching mathematics curricula from the viewpoint of teachers in the Governorate of Al Dhahirah, Sultanate of Oman. The researcher adopted the descriptive-analytical approach. To collect the needed data, a questionnaire of two dimensions was used. It includes (13) items to measure the effectiveness of using the Google classroom in teaching mathematics curricula from the teacher's point of view and includes (10) items to measure the difficulties of using the Google classroom in teaching mathematics curricula from the teachers' point of view. These tools were applied to (32) male and (31) female as the study sample. They represent mathematics teachers in public schools in the Al Dhahirah Governorate for the first semester of the 2020/2021 academic year. The results of the study revealed that the arithmetic average of the activity axis as a whole (3.41) with a high degree of effectiveness, and the arithmetic average for the axis of difficulties as a whole was (3.79) with a high evaluation score as well. There is no statistical significance difference at the level of (α = 0.05) in the responses of the sample members due to gender. However, there are differences of similar significance due to the variable of teaching experience in favor of the group (10-20 years). In light of the results, the study recommended providing adequate training for male and female teachers about the use and employment of the Google Classroom educational platform in the educational process in general and in teaching mathematics curricula in particular, raising the awareness of the role of electronic educational platforms in developing the educational process, keeping pace with the scientific and the technological development